Central Venous Catheter as a Novel Approach to Postoperative Thrombolysis in Patients with Acute Iliofemoral Deep Venous Thrombosis - Biyun Teng; Fenghe Li; Xuehu Wang; Hao Tian; Yu Zhao; Qiu Zeng (Clinical and Experimental Hypertension, 2023)
Background and aims Percutaneous mechanical thrombectomy (PMT) along with postoperative thrombolysis (POT) has been the standard treatment for acute iliofemoral deep venous thrombosis (IFDVT). However, commonly used catheter directed thrombolysis (CDT) approaches for POT carry certain disadvantages, including the need for a sheath, inferior comfortability, and catheter-related complications. Therefore, we propose a new simplified method of POT using a central venous catheter (CVC). Methods The retrospective study analyzed patients with IFDVT who underwent POT using CVC from January 2020 to August 2021. The treatment modalities included filter placement, thrombus removal, iliac vein obstruction release, postoperative CVC thrombolysis, filter retrieval, and adequate full course anticoagulation. Results A total of 39 patients were included in this retrospective study. All patients underwent PMT surgery with a procedure success rate of 100%. In the post-PMT CVC thrombolysis, the puncture sites were located in the below-knee vein, including 58.97% in the peroneal vein. The mean duration of CVC-directed thrombolysis was 3.69 ± 1.08 days, and the total urokinase dose was 2.27 ± 0.71 MIU. A total of 37 patients (94.87%) had successful thrombolysis with a length of hospital stay of 5.82 ± 2.21 days. During CVC-directed thrombolysis, only four minor bleeding complications occurred, two of which were indwelling catheter-related. During the 12-month follow-up period, the patency rate and post-thrombotic syndrome incidences were 97.44% and 2.56%, respectively. Conclusion Thrombolysis through a CVC is a feasible, safe, and effective POT method, and could be an alternative to the conventional CDT approach for patients with IFDVT.